Making Emotional Connections in the Age of Neoliberalism. (June 2016) - Bialostok, Steven M.; Aronson, Matt
Abstract: Emotional expression, long derided as inimical to material success in the context of industrializing capitalism, now is seen in pedagogical circles as crucial to children's development into workers and citizens. Moving away from an emphasis on market rationality's so‐called person of reason, post‐Fordist economic environments increasingly venerate the less tangible "person of affect." This study theorizes that a teacher's own emotional discourse shapes children's subjectivities and that this process corresponds with late capitalism's needs for workers who are reflexive and emotionally adept. Our analysis shows how the teacher uses emotional expression to accomplish a pedagogical goal, namely that of encouraging children to name and to know their own emotionality so they can better manage the "when and where" of its expression in other contexts, most especially the workplace. Children who effectively deploy these "softer" aspects of the self now represent yet another facet of entrepreneurial (neoliberal) subjectivity.